Managing irrigation jointly with farmers: history, present status and future: review of participatory irrigation management in Sri Lanka - Jinapala, K.; Premadasa, L.; Somaratne, Pallewatte G.; Samad, Madar (2010)
Agriculture development has been the main strategy for the socioeconomic development in the country since time immemorial, even though its contribution to GDP has been declining recently. Successive governments of Sri Lanka since independence have invested heavily in the irrigated agriculture sector to address the food security concerns of the country. The continuous investment in irrigation was required to address problems such as spatial and temporal variations in monsoonal rainfall in the country, which has a serious negative impact on food production and livelihoods of people. The need for pursuing irrigation development and management has become more important in the country in the face of rapid population growth and increasing food prices in the world market. In this context, managing irrigation schemes for productivity increase is becoming increasingly important and different irrigation management models have also emerged through attempts made in this direction by countries including Sri Lanka, where irrigation plays a leading role in food production and nation development. Farmers? active involvement in irrigation management, especially operation and maintenance (O&M) and decision-making as well, has been identified as a key requirement to attain productivity goals and the sustainability of irrigation systems. This paper aims at reviewing participatory irrigation management approaches adopted in medium and major irrigation systems in Sri Lanka with a view to identifying their past and present trends and future directions. The review will contribute to an improved understanding by policymakers, managers of irrigation schemes and farmers of the role of participatory irrigation management, its past and present including institutional structures, responsibilities and performance and the directions it should take to meet future challenges as a dynamic institutional mechanism. As all the medium and major irrigation schemes in the country are jointly managed by farmers and government agencies, the inferences drawn from the review would be important for the agencies and farmers alike to introduce necessary changes in their programs to address future needs and requirements.